Use of Supramolecular Assemblies as Lithographic Resists. (15th May 2017) - Lewis, Scott M.; Fernandez, Antonio; DeRose, Guy A.; Hunt, Matthew S.; Whitehead, George F. S.; Lagzda, Agnese; Alty, Hayden R.; Ferrando‐Soria, Jesus; Varey, Sarah; Kostopoulos, Andreas K.; Schedin, Fredrik; Muryn, Christopher A.; et al.
Abstract: A new resist material for electron beam lithography has been created that is based on a supramolecular assembly. Initial studies revealed that with this supramolecular approach, high‐resolution structures can be written that show unprecedented selectivity when exposed to etching conditions involving plasmas.